IMPLEMENTASI PENDIDIKAN AGAMA DAN KEAGAMAAN PASCA KONFLIK DI KOTA AMBON - Makkulawu Makkulawu (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This research aims to describe the implication of social conflict to educationof religion (formal and informal) implementation. This was conductedat Ambon, Maluku. Data was collected by depth interview andobservation.This research indicates that situation of Ambon today is normally. Learningactivity (especially learning in religion subject) in school andmadrasah is running well. Local government had been renovate almostschool that was damaged by social conflict